The Aesthetics of Kaia Dance in the Socio-Cultural Context of the Laban Community, Salido, Pesisir Selatan - Irdawati, Irdawati (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
This study aims to explore the aesthetics of the Kaia Dance in the socio-cultural context of the Laban community, Kenagarian Salido, IV Jurai District, Pesisir Selatan Regency, West Sumatra. The method employed is a qualitative approach with analytical description, where all data, both written and field data, are described and analyzed according to the research problem. The aesthetic theories of A.A.M. Djelantik and Deni Junaedi are used to examine the issues, while Y. Sumandyo Hadi's perspective is applied to analyze the dance form. Kaia Dance is a traditional dance that has evolved in the Laban community, Kenagarian Salido. It embodies aesthetic elements reflecting the struggle to provide for one's family and draws inspiration from the surrounding nature and local conditions. This study provides new insights into understanding the Kaia Dance as a complex medium of expression, not only in terms of its movements but also in its rich social symbolism and local aesthetic values. The aesthetic values in Kaia Dance can be observed through three aspects: aesthetic object, aesthetic subject, and aesthetic value